2018
DOI: 10.3174/ajnr.a5504
|View full text |Cite
|
Sign up to set email alerts
|

What Have We Learned from Perfusion MRI in Multiple Sclerosis?

Abstract: SUMMARY: Using MR imaging, perfusion can be assessed either by dynamic susceptibility contrast MR imaging or arterial spin-labeling. Alterations of cerebral perfusion have repeatedly been described in multiple sclerosis compared with healthy controls. Acute lesions exhibit relative hyperperfusion in comparison with normal-appearing white matter, a finding mostly attributed to inflammation in this stage of lesion development. In contrast, normal-appearing white and gray matter of patients with MS has been mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
51
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 59 publications
(56 reference statements)
0
51
0
5
Order By: Relevance
“…Most interesting, when we compared MS phenotypes, a reduction in rCBV values of the caudate nuclei in patients with PMS compared with RRMS was proved. Different mechanisms could explain this finding, mainly related to a decreased neuronal metabolic demand secondary to atrophy, 13,30 though primary neuronal meta-bolic dysfunctions and alterations of cerebral vasculature have also been proposed. 13,30 Finally, at the QSM analysis, patients with MS showed a significant reduction of magnetic susceptibility values in the thalamus compared with HC, in line with recent quantitative MR imaging studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interesting, when we compared MS phenotypes, a reduction in rCBV values of the caudate nuclei in patients with PMS compared with RRMS was proved. Different mechanisms could explain this finding, mainly related to a decreased neuronal metabolic demand secondary to atrophy, 13,30 though primary neuronal meta-bolic dysfunctions and alterations of cerebral vasculature have also been proposed. 13,30 Finally, at the QSM analysis, patients with MS showed a significant reduction of magnetic susceptibility values in the thalamus compared with HC, in line with recent quantitative MR imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Along with volume loss, a wide range of pathologic changes affecting the DGM of patients with MS has been also demonstrated using different advanced MR imaging techniques. In particular, DTI studies showed the presence of microstructural damage in these structures, [6][7][8][9] while PWI and Quantitative Susceptibility Mapping (QSM) studies described decreased cerebral perfusion [10][11][12][13] and a complex pattern of susceptibility changes [14][15][16][17] affecting the DGM of patients with MS, respectively.…”
mentioning
confidence: 99%
“…Multiple sclerosis may also increase the relative size of the PVS due WM atrophy 23 , and PVS size is also known to increase with age 24 . Moreover, CBF and CBV were generally found to be reduced in the normal appearing white matter in MS 25 . While the finding that PVS have an influence on DSC measurements remains valid, the size of the PVS estimated herein should therefore not be generalized to other populations.…”
Section: Discussionmentioning
confidence: 96%
“…However, the total blood volume in WM is only about 2.6%, resulting in a venous WM blood volume of less than 2%. Moreover, the blood volume in NAWM of patients with MS is only marginally lower relative to controls Diffusion of the proton spins was not taken into account and the signal loss was assumed to be dominated by static dephasing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the blood volume in NAWM of patients with MS is only marginally lower relative to controls. 75 5. Diffusion of the proton spins was not taken into account and the signal loss was assumed to be dominated by static dephasing.…”
mentioning
confidence: 99%